High-entropy glass scintillator material, preparation method and application thereof

CN122978174APending Publication Date: 2026-10-27NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611077179.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但该类材料结构稳定性较差,对环境温湿度变化高度敏感,在存储及服役过程中易发生相态转变、自发析晶,使高透光玻璃态转变为低透光晶态,造成透光率与光电转换效率大幅下降,严重的光散射引发了成像模糊、探测误差增大等问题,无法满足工业长期服役、复杂工况监测的使用需求,难以实现大规模工程化应用

Benefits of technology

(1)本发明提供的高熵玻璃闪烁体材料具备优异的抗析晶特性,其化学结构通式为[PPh3(CnH2n+1)]2MX4,与非高熵玻璃闪烁体相比,本发明通过将传统单组份玻璃闪烁体高熵化,使其能够一直稳定在无序的玻璃态,将单组份玻璃闪烁体的稳定时间从1天大幅延长至150天,从而使玻璃闪烁体能够更加适配于苛刻的工业应用场所。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978174A_ABST
    Figure CN122978174A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of light-emitting materials, and particularly discloses a high-entropy glass scintillator material, a preparation method and application thereof, the high-entropy glass scintillator material has excellent anti-crystallization characteristics, a chemical structure general formula is [PPh3(C n H 2n+1 )]2MX4, compared with non-high-entropy glass scintillators, the application can keep the traditional single-component glass scintillators in a disordered glass state by high-entropy, can greatly extend the stable time of the single-component glass scintillators from 1 day to 150 days, and thus the glass scintillators can be more suitable for harsh industrial application sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of luminescent materials technology, specifically to a high-entropy glass scintillator material, its preparation method, and its applications. Background Technology

[0002] Scintillators are core optoelectronic functional materials for converting radiation energy into visible light photon energy. As the core medium in systems such as X-ray imaging, radiation detection, photodynamic therapy, and industrial radiation monitoring, their photoelectric conversion efficiency, transmittance, structural stability, and fabrication process characteristics directly determine the imaging accuracy, detection sensitivity, and long-term service reliability of the equipment. With the rapid development of fields such as medical diagnostics, industrial non-destructive testing, and wearable dose monitoring, the industry's requirements for the comprehensive performance, fabrication cost, environmental safety, and operational stability of scintillator materials are continuously increasing. Developing scintillator materials that combine high performance, low cost, environmental friendliness, and high stability has become a core research hotspot in this field.

[0003] While currently used inorganic scintillators possess excellent photoelectric conversion performance and thermal stability, they suffer from numerous unavoidable technical drawbacks. Existing inorganic scintillators primarily rely on high-temperature solid-state reactions and chemical vapor deposition processes, which are complex, energy-intensive, and have long production cycles, significantly increasing industrialization costs. Furthermore, inorganic scintillators containing heavy metals are prone to radioactive isotope accumulation under long-term high-energy irradiation, leading to material performance degradation and decreased detection accuracy, severely limiting their application in sensitive fields such as biomedicine and precision civilian detection. To address these shortcomings of inorganic scintillators, the industry has developed organic-inorganic hybrid glassy scintillators. This material offers advantages such as low-temperature processing capability, simple molding, environmental friendliness, and no heavy metal pollution, effectively compensating for the shortcomings of traditional inorganic scintillator preparation and environmental protection. However, this type of material has poor structural stability and is highly sensitive to changes in environmental temperature and humidity. During storage and service, it is prone to phase transitions and spontaneous crystallization, which causes the high-transmittance glass state to transform into a low-transmittance crystalline state, resulting in a significant decrease in transmittance and photoelectric conversion efficiency. Severe light scattering leads to problems such as blurred imaging and increased detection errors, making it unable to meet the needs of long-term industrial service and complex working condition monitoring, and difficult to achieve large-scale engineering applications.

[0004] Therefore, there is an urgent need in this field to develop a new type of glassy X-ray scintillator that can overcome the defects of existing technologies and has both structural stability and high imaging accuracy, so as to break through the limitations of existing technologies and adapt to the needs of high-end applications in multiple scenarios. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a high-entropy glass scintillator material, its preparation method, and its applications.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A high-entropy glass scintillator material, wherein the chemical formula of the scintillator material is [PPh3(C n H 2n+1 )]2MX4, the structure is as follows: Where n = 2, 3, 4, 5 and 6; M is selected from Mn, Zn, Cd, Cu, Pb, or Sn; X is selected from Cl, Br, or I.

[0007] The present invention provides a method for preparing the above-mentioned high-entropy glass scintillator material, comprising the following steps: dissolving a halogen metal salt in an organic solvent, then adding ethyltriphenylphosphine bromide, propyltriphenylphosphine bromide, butyltriphenylphosphine bromide, pentyltriphenylphosphine bromide and hexyltriphenylphosphine bromide, heating to react, and after the reaction is completed, cooling to room temperature to obtain the high-entropy glass scintillator material.

[0008] Specifically, the molar ratio of ethyltriphenylphosphine bromide, propyltriphenylphosphine bromide, butyltriphenylphosphine bromide, pentyltriphenylphosphine bromide, hexyltriphenylphosphine bromide and halogen metal salt is 1:1:1:1:1:1-5.

[0009] Specifically, the molar volume ratio of the halogen metal salt to the organic solvent is 0.01 mol: 5-15 mL.

[0010] Specifically, the metal element in the halide metal salt is selected from Mn, Zn, Cd, Cu, Pb or Sn; the halogen element in the halide metal salt is selected from Cl, Br or I.

[0011] Specifically, the organic solvent is selected from at least one of dichloromethane, ethanol, methanol, and N,N-dimethylformamide.

[0012] Specifically, the heating temperature is 200-250℃, and the heating time is 10-30 minutes.

[0013] This invention provides the application of the above-mentioned high-entropy glass scintillator material in X-ray detection and imaging.

[0014] The present invention also provides the application of the above-mentioned high-entropy glass scintillator material in the preparation of light-emitting conversion layer materials for doped or undoped LED devices.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The high-entropy glass scintillator material provided by the present invention has excellent anti-crystallization properties, and its general chemical formula is [PPh3(C n H 2n+1Compared with non-high-entropy glass scintillators, this invention increases the entropy of traditional single-component glass scintillators, enabling them to remain stable in a disordered glass state. This significantly extends the stabilization time of single-component glass scintillators from 1 day to 150 days, making glass scintillators more suitable for harsh industrial applications.

[0016] (2) The high-entropy glass scintillator material provided by this invention has excellent scintillation performance, with a minimum detection limit of 16.53 nGy / s, which is about 332 times lower than the detection limit required by typical medical imaging systems (5500 nGy / s), and a spatial resolution of up to 28.3 lp mm. -1 These properties enable scintillator materials to achieve high-resolution static imaging as well as real-time dynamic X-ray imaging. Attached Figure Description

[0017] Figure 1 The figures show the characterization results of the thermal and entropy properties of the scintillator materials prepared in Example 1 and Comparative Examples 1-2 of the present invention, where a is the DSC thermal analysis curve of the three types of samples; b is the entropy value calculated based on the glass transition portion of the DSC curve; and c is the theoretical entropy value calculated based on the empirical equation. Figure 2 The images show the luminescence properties of the scintillator materials prepared in Example 1 and Comparative Example 2 of this invention, where a is the photoluminescence spectrum of the two materials under ultraviolet excitation at a wavelength of 360 nm; and b is the luminescence lifetime diagram of HEG. Figure 3 The image shows a comparison of the luminescence properties of the scintillator material prepared in Example 1 of this invention and the commercial scintillator LYSO. In the image, a is a comparison of the spectra under X-ray irradiation at a voltage of 50 kV and a dose rate of 278 mGy / s, and b is a graph showing the change of RL intensity and transmittance of HEG over time. Figure 4 The radiative luminescence intensity and dose rate of the scintillator material prepared in Example 1 of this invention; Figure 5 The transmittance spectra of the scintillator materials prepared in Example 1 and Comparative Example 2 of the present invention are as follows: a is the transmittance spectrum of HEG in its fresh preparation state and after continuous exposure to environmental conditions for 150 days, and b is the transmittance spectrum of SCG glass scintillator in its fresh preparation state and after exposure to environmental conditions for 1 day. Figure 6 These are comparative radiation imaging images of the scintillator materials prepared in Example 1 and Comparative Example 2 of the present invention after being placed for different periods of time. Figure 7 These are comparative photographs showing the evolution of the scintillator materials prepared in Example 1 and Comparative Examples 1-2 of the present invention over time. Detailed Implementation

[0018] The present invention will be further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0019] It should be noted that, unless otherwise specified, all chemical reagents involved in this invention were purchased through commercial channels.

[0020] Example 1 A method for preparing a high-entropy glass scintillator material includes the following steps: Manganese bromide tetrahydrate (1.43 g, 0.005 mol) was dissolved in methanol (5 mL). Then, ethyltriphenylphosphine bromide, propyltriphenylphosphine bromide, butyltriphenylphosphine bromide, pentyltriphenylphosphine bromide, and hexyltriphenylphosphine bromide were added to methanol in a molar ratio of 1:1:1:1:1 (total 3.96 g, 0.01 mol). After stirring magnetically for 5 minutes, the solution was added to a silica gel bath. The silica gel bath was heated to 240 °C and heated for 10 minutes. The silica gel bath was then removed from the heating stage and cooled at room temperature to obtain the high-entropy glass scintillator material, denoted as HEG.

[0021] Example 2 A method for preparing a high-entropy glass scintillator material includes the following steps: Manganese bromide tetrahydrate (0.57 g, 0.002 mol) was dissolved in methanol (5 mL). Then, ethyltriphenylphosphine bromide, propyltriphenylphosphine bromide, butyltriphenylphosphine bromide, pentyltriphenylphosphine bromide, and hexyltriphenylphosphine bromide were added to methanol in a molar ratio of 1:1:1:1:1 (total 3.96 g, 0.01 mol). After stirring magnetically for 5 minutes, the solution was added to a silica gel bath. The silica gel bath was heated to 240°C and heated for 10 minutes. The silica gel bath was then removed from the heating table and cooled at room temperature to obtain the high-entropy glass scintillator material.

[0022] Example 3 A method for preparing a high-entropy glass scintillator material includes the following steps: Manganese bromide tetrahydrate (2.87 g, 0.01 mol) was dissolved in methanol (5 mL). Then, ethyltriphenylphosphine bromide, propyltriphenylphosphine bromide, butyltriphenylphosphine bromide, pentyltriphenylphosphine bromide, and hexyltriphenylphosphine bromide were added to methanol in a molar ratio of 1:1:1:1:1 (total 3.96 g, 0.01 mol). After stirring magnetically for 5 minutes, the solution was added to a silica gel bath. The silica gel bath was heated to 240 °C and heated for 10 minutes. The silica gel bath was then removed from the heating platform and cooled at room temperature to obtain the high-entropy glass scintillator material.

[0023] Comparative Example 1 A method for preparing a two-component glass scintillator material includes the following steps: Manganese bromide tetrahydrate (1.43 g, 0.005 mol) was dissolved in methanol (5 mL). Then, ethyltriphenylphosphine bromide and propyltriphenylphosphine bromide were added to methanol in a 1:1 molar ratio (total 3.77 g, 0.01 mol). After stirring magnetically for 5 minutes, the solution was added to a silica gel bath. The silica gel bath was heated to 240°C and heated for 10 minutes. The silica gel bath was then removed from the heating table and cooled at room temperature to obtain the two-component glass scintillator material, denoted as DCG.

[0024] Comparative Example 2 A method for preparing a single-component glass scintillator material includes the following steps: Manganese bromide tetrahydrate (1.43 g, 0.005 mol) was dissolved in methanol (5 mL), and then propyltriphenylphosphine bromide (3.85 g, 0.01 mol) was added to the methanol. After stirring magnetically for 5 minutes, the solution was added to a silica gel bath. The silica gel bath was heated to 240°C and heated for 10 minutes. The silica gel bath was then removed from the heating table and cooled at room temperature to obtain a single-component glass scintillator material, denoted as SCG.

[0025] The characterization results of the thermal and entropy properties of the scintillator materials prepared in Example 1 and Comparative Examples 1-2 of this invention are shown in the figure below. Figure 1 As shown in the figure, a represents the DSC thermal analysis curves of the three types of samples; b represents the entropy value calculated from the glass transition portion of the DSC curve; and c represents the theoretical entropy value calculated based on the empirical equation. The figure shows that as the composition of the glass scintillator increases, the cold crystallization peak is suppressed. When it becomes a high-entropy scintillator, the cold crystallization peak disappears along with the melting peak. This clearly demonstrates that as the composition increases, the entropy enhancement can effectively improve the glass's resistance to structural order and further enhance its anti-crystallization stability. The activation energy (Ea) was calculated using the Kissinger equation, yielding a HEG value of 15464 J·mol⁻¹. -1 The value of SCG is 16231 J·mol. -1 The configurational entropy (ΔS) of the glass scintillator material was also calculated from the glass transition. The measured entropy values ​​were 7.16 × 10⁻⁶. -4 JK -1 (SCG), 1.19×10 -3 JK -1 (DCG) and 2.78 × 10 -3 JK -1 (HEG) shows that the entropy value of the scintillator material increases with the number of components, which is in very good agreement with the theoretical value.

[0026] The luminescence performance diagrams of the scintillator materials prepared in Example 1 and Comparative Example 2 of this invention are shown in the figure below. Figure 2 As shown in the figure, a is the photoluminescence spectrum of the two materials under xenon lamp irradiation at a wavelength of 360 nm; b is the luminescence lifetime of HEG. It can be seen from the figure that the increase in the number of components did not change the position of the emission peak, which remained at 520 nm. Under 365 nm excitation, the luminescence lifetime of HEG was measured to be 236.45 μs.

[0027] The comparison diagram of the luminescence performance of the scintillator material prepared in Example 1 of this invention and the commercial scintillator LYSO is shown in the figure below. Figure 3 As shown in the figure, a is a comparison of the spectra under X-ray irradiation at a voltage of 50 kV and a dose rate of 278 mGy / s, and b is a graph showing the change of RL intensity and transmittance of HEG over time. It can be seen from the figure that HEG has excellent RL intensity, and its luminescence intensity is higher than that of the currently commercial scintillator LYSO. HEG also has good radiative luminescence stability. After being placed in an air environment for 150 days, the radiative luminescence intensity still has 98% of the initial value, and the optical linear transmittance still remains above 78%.

[0028] The radiative luminescence intensity and dose rate of the scintillator material prepared in Example 1 of this invention are as follows: Figure 4 As shown in the figure, HEG exhibits excellent scintillation performance, with a detection limit of 16.53 nGy / s. This value is approximately 332 times lower than the detection limit required by typical medical imaging systems (5500 nGy / s), and the spatial resolution reaches 28.3 lp mm. -1 These properties enable scintillator materials to achieve high-resolution static imaging as well as real-time dynamic X-ray imaging.

[0029] The transmittance spectra of the scintillator materials prepared in Example 1 and Comparative Example 2 of this invention as a function of time are as follows: Figure 5 As shown in the figure, a is the transmittance spectrum of HEG in its fresh preparation state and after 150 days of continuous exposure to environmental conditions, and b is the transmittance spectrum of SCG glass scintillator in its fresh preparation state and after 1 day of exposure to environmental conditions. It can be seen from the figure that after SCG is placed in the air environment for 1 day, the transmittance of SCG drops rapidly, while after HEG is placed in the air environment for 150 days, the transmittance of HEG only drops by 2-3%.

[0030] The radiation imaging comparison images of the scintillator materials prepared in Example 1 and Comparative Example 2 of this invention after being placed for different times are shown below. Figure 6As shown in the figure, after SCG was placed in an air environment for 1 day, its X-ray image became very blurry, and the internal structure of the chip could not be identified. Even after HEG was placed in an air environment for 150 days, its X-ray image remained very clear, and the internal circuit structure of the chip could be clearly identified.

[0031] Comparative photographs of the evolution of the scintillator materials prepared in Example 1 and Comparative Examples 1-2 over time are shown below. Figure 7 As shown in the figure, SCG began to crystallize after being placed in an air environment for 1 day; DCG began to crystallize after being placed in an air environment for 30 days; and HEG remained in a glassy state even after being placed in an air environment for 150 days.

[0032] Finally, it should be noted that the above embodiments do not limit the present invention in any way. Those skilled in the art can make modifications and improvements based on the present invention. Therefore, any modifications or improvements made without departing from the spirit of the present invention are within the scope of protection claimed by the present invention.

Claims

1. A high-entropy glass scintillator material, characterized in that, The chemical formula of the scintillator material is [PPh3(C n H 2n+1 )]2MX4, the structure is as follows: Where n = 2, 3, 4, 5 and 6; M is selected from Mn, Zn, Cd, Cu, Pb, or Sn; X is selected from Cl, Br, or I.

2. The method for preparing the high-entropy glass scintillator material as described in claim 1, characterized in that, The process includes the following steps: dissolving a halogen metal salt in an organic solvent, then adding ethyltriphenylphosphine bromide, propyltriphenylphosphine bromide, butyltriphenylphosphine bromide, pentyltriphenylphosphine bromide, and hexyltriphenylphosphine bromide, heating the mixture to react, and cooling it to room temperature after the reaction is complete to obtain the high-entropy glass scintillator material.

3. The preparation method according to claim 2, characterized in that, The molar ratio of ethyltriphenylphosphine bromide, propyltriphenylphosphine bromide, butyltriphenylphosphine bromide, pentyltriphenylphosphine bromide, hexyltriphenylphosphine bromide, and the halogen metal salt is 1:1:1:1:1:1-5.

4. The preparation method according to claim 2, characterized in that, The molar volume ratio of the halogen metal salt to the organic solvent is 0.01 mol: 5-15 mL.

5. The preparation method according to claim 2, characterized in that, The metal element in the halogen metal salt is selected from Mn, Zn, Cd, Cu, Pb or Sn; the halogen element in the halogen metal salt is selected from Cl, Br or I.

6. The preparation method according to claim 2, characterized in that, The organic solvent is selected from at least one of ethanol, methanol, and N,N-dimethylformamide.

7. The preparation method according to claim 2, characterized in that, The heating temperature for the reaction is 200-250℃, and the heating time is 10-30 minutes.

8. The application of the high-entropy glass scintillator material as described in claim 1 in X-ray detection and imaging.

9. The application of the high-entropy glass scintillator material as described in claim 1 in the preparation of light-emitting conversion layer materials for doped or undoped LED devices.